2012
DOI: 10.1021/jm300426q
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Evaluation of pH-Dependent Hydrolyzable Emetine Analogues as Treatment for Prostate Cancer

Abstract: The N-2′ position of the natural product emetine has been derivatized to thiourea, urea, sulfonamide, dithiocarbamate, carbamate and pH responsive hydrolysable amide analogs. In-vitro studies of these analogs in PC3 and LNCaP prostate cancer cell lines showed that the analogs are generally less cytotoxic (average IC50 ranging from 0.079 μM to 10 μM) than emetine (IC50 ranging from 0.0237 to 0.0329 μM). The pH sensitive sodium dithiocarbamate salt 13 and the amide analogs 21, 22, 26 (obtained from maleic and ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 28 publications
(60 reference statements)
3
50
0
Order By: Relevance
“…Further, when 33 mg/kg body weight of emetine or compound 1 was administered, mice that received emetine were lethargic and showed about four times weight loss compared with control; while, mice that received compound 1 appeared healthy and did not show any significant difference in weight compared with control. 15 These results encouraged us to pursue further anticancer evaluation of derivatives of compound 1 similar to compound 2. We were interested in developing more stable analogs that would not necessarily act as prodrugs, but would retain anticancer activities while minimizing the toxicities associated with emetine.…”
Section: Biologymentioning
confidence: 98%
See 1 more Smart Citation
“…Further, when 33 mg/kg body weight of emetine or compound 1 was administered, mice that received emetine were lethargic and showed about four times weight loss compared with control; while, mice that received compound 1 appeared healthy and did not show any significant difference in weight compared with control. 15 These results encouraged us to pursue further anticancer evaluation of derivatives of compound 1 similar to compound 2. We were interested in developing more stable analogs that would not necessarily act as prodrugs, but would retain anticancer activities while minimizing the toxicities associated with emetine.…”
Section: Biologymentioning
confidence: 98%
“…In addition, any substituted group would result in conformational changes which appear to affect the space between the tricyclic and bicyclic ring system of emetine and consequently affect the bioactivity of the resulting analog including protein synthesis inhibitory and anticancer activities. 5,15,20 Hence, an appropriate substituent in this position would result in a clinically useful emetine prodrug, or an emetine derivative that does not have the same systemic toxicity as emetine. We are currently studying a diverse library of emetine analogs in this regard.…”
Section: Biologymentioning
confidence: 99%
“…It is evident that all the N-2′ derived emetine derivatives have a significantly reduced cytotoxicity. 69 However, our in vivo studies show that while some of these derivatives do not produce acute lethal toxicity like emetine, some of them are still toxic. We propose here that the in vivo toxicity (cardiotoxicity, lethality) of emetine, and its derivatives may not be controlled by the N-2′ secondary amine alone but by the solution phase conformation adopted by the molecule.…”
Section: Discussionmentioning
confidence: 87%
“…2,5 To identify emetine derivatives with reduced systemic toxicity, we have performed structure activity relationship (SAR) studies on N-2′ modified derivatives of emetine with diverse substituents. 69 We have shown that modification at the N-2′ causes emetine to become significantly less cytotoxic (i.e. up to 300-fold reduction).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation